2021
DOI: 10.3390/ijms22115672
|View full text |Cite
|
Sign up to set email alerts
|

Could Histamine H1 Receptor Antagonists Be Used for Treating COVID-19?

Abstract: COVID-19 has rapidly become a pandemic worldwide, causing extensive and long-term health issues. There is an urgent need to identify therapies that limit SARS-CoV-2 infection and improve the outcome of COVID-19 patients. Unbalanced lung inflammation is a common feature in severe COVID-19 patients; therefore, reducing lung inflammation can undoubtedly benefit the clinical manifestations. Histamine H1 receptor (H1 receptor) antagonists are widely prescribed medications to treat allergic diseases, while recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 107 publications
0
16
0
Order By: Relevance
“…Furthermore, this mast cell activation was associated with interstitial edema and immunothrombosis [ 27 ], while the levels of the mast cell-specific protease, chymase, correlated significantly with disease severity [ 23 ]. Moreover, studies have reported that H1 as well as H2 receptor antagonists, such as famotidine, are associated with a reduced risk of infection and deterioration leading to intubation or death from COVID-19 [ 28 , 29 ]. These agents are considered to improve pulmonary symptoms of SARS-CoV-2 infection by blocking the histamine-mediated cytokine storm [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this mast cell activation was associated with interstitial edema and immunothrombosis [ 27 ], while the levels of the mast cell-specific protease, chymase, correlated significantly with disease severity [ 23 ]. Moreover, studies have reported that H1 as well as H2 receptor antagonists, such as famotidine, are associated with a reduced risk of infection and deterioration leading to intubation or death from COVID-19 [ 28 , 29 ]. These agents are considered to improve pulmonary symptoms of SARS-CoV-2 infection by blocking the histamine-mediated cytokine storm [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The H2 antagonist showed molecular recognition in the central S1-S1′/S2 subpockets ( Figure 5 D), while the androgen receptor antagonist showed a completely different binding mode ( Figure 5 M), where the 4-fluorobenzenesulfonyl substituent was oriented beyond the S1′ subpocket, reaching hydrophobic interactions in a small cavity formed by Thr24, Thr45 and Ser46 ( Figure S2 ), which until now has not been fully explored in the design of new inhibitors [ 54 ]. Experimental evidence indicates that histamine receptor antagonists can inhibit SARS-CoV-2 through the H1 receptor or the ACE2 receptor, and can also interrupt the interaction between heparan sulfate and the spike protein, slowing the entry of genetic material of SARS-CoV-2 [ 55 ]. On the other hand, it has been suggested that the combination of antagonists of the H1, H2 and H4 receptors is effective in reducing lung inflammation caused by SARS-CoV-2, reducing the severity of the infection [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The rationale for their use is that the virus directly activates mast cells (expressing ACE2) secreting histamine in COVID‐19 pneumonia and that several anti‐histamines prevent SARS‐CoV2 entry in in vitro models. 64 , 65 In addition, patients treated with these drugs are more resistant to SARS‐CoV2, and cetirizine and famotidine alleviate pulmonary symptoms in COVID‐19. 66 These data, confirming the protective effects toward SARS‐CoV2 infection of several anti‐inflammatory drugs, underline that AAD and allergy share some pathogenic mechanisms with COVID‐19.…”
Section: Immuno‐pathogenesis Of Covid‐19mentioning
confidence: 99%
“…The control of SARS‐CoV2 infection in respiratory allergy may also be due to anti‐histamine drugs. The rationale for their use is that the virus directly activates mast cells (expressing ACE2) secreting histamine in COVID‐19 pneumonia and that several anti‐histamines prevent SARS‐CoV2 entry in in vitro models 64,65 . In addition, patients treated with these drugs are more resistant to SARS‐CoV2, and cetirizine and famotidine alleviate pulmonary symptoms in COVID‐19 66 .…”
Section: Immuno‐pathogenesis Of Covid‐19mentioning
confidence: 99%